2015
DOI: 10.1007/s12522-015-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of elevated thyroid stimulating hormone on female subfertility

Abstract: We found an association between elevated TSH and the decreased rate of clinical pregnancy. This might be related to an ovulatory disorder and pathophysiology of unexplained infertility. These results may reinforce the usefulness of TSH screening in infertility population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In a cross sectional study of 5000 Belgian women (mean age: 32.0, SD: 5.5 years), there were no significant association, between ovarian reserve, thyroid hormones and thyroid autoimmunity [9]. Several studies also show an inverse association between ovarian reserves, hypothyroidism and thyroid autoimmunity in humans and animals [10, 11]; however to the best of our knowledge, the interaction between changes in thyroid functions and ovarian reserves status has not yet been reported and it is unclear whether or not women with poor ovarian reserves are at increased risk of occurrence of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross sectional study of 5000 Belgian women (mean age: 32.0, SD: 5.5 years), there were no significant association, between ovarian reserve, thyroid hormones and thyroid autoimmunity [9]. Several studies also show an inverse association between ovarian reserves, hypothyroidism and thyroid autoimmunity in humans and animals [10, 11]; however to the best of our knowledge, the interaction between changes in thyroid functions and ovarian reserves status has not yet been reported and it is unclear whether or not women with poor ovarian reserves are at increased risk of occurrence of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is an association between thyroid autoimmunity and infertility [ 29 , 30 ]. Human and animal studies have shown that there is a negative correlation between ovarian reserve and thyroid autoimmunity [ 31 , 32 ]. A case-control study found that AITD is independently associated with AMH and that women with AITD have lower AMH than in the control group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some guidelines and review studies suggest that it is preferable for a woman who wishes to become pregnant to maintain serum TSH concentrations <2.5 mIU/L, and this level should be preserved during the first and second trimesters of pregnancy ( 41 , 42 ). The harm of TSH levels above normality (>4.5 mIU/L) is attested by some studies that, by means of multivariate analysis, found a positive correlation between high TSH levels and decreased clinical pregnancy rates, although the same correlation has not been attested for the frequency of miscarriages and live births ( 25 , 43 ). Hyperthyroidism, marked by low serum TSH levels, is also related to decreased rates of live births ( 5 ).…”
Section: Discussionmentioning
confidence: 99%